Adesão bacteriana e formação inicial de biofilme em diferentes superfícies de bráquetes ortodônticos - Bressan, Michelli (2015)
Objective: The objective was to determine which bracket surface (metal or ceramic) promotes higher adherence and biofilm development. Material and Methods: This study evaluated the development and bacterial adhesion on different brackets surfaces metal and ceramic after 12 and 24 hours of incubation. The microcosm technique was used. The saliva collected from the patient was prepared, stored and inoculated on the brackets. After one hour, the saliva was removed and mean DMM was added in the recipient. The brackets were incubated under anaerobic conditions for 12 and 24 hours at 37°C for biofilm growth. After this period, the brackets were removed from the plate with sterilized tweezers, sonicated to disperse the cells. Serial dilutions were performed to 1:10-7 incubated at 37°C for 120 hours for count colony forming units. Results: Statistical analysis showed no significant difference of the number of colony forming units between groups. Conclusion: Based on the results obtained in this study and respecting the limitations, it can be concluded that, since there is no difference in bacterial growth at 12 and 24 hours, the most appropriate bracket to each case should be selected by the professional, based on aesthetic needs and the brackets mechanical behavior.